Asymptotic methods in the theory of nonlinear random oscillations - Kolomiyets, V. G.; Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study applications of asymptotic methods of nonlinear mechanics and the method of Fokker-Planck-Kolmogorov equations to the investigation of random multifrequency oscillations in systems with many degrees of freedom.